1993
DOI: 10.1002/1097-0142(19930501)71:9<2862::aid-cncr2820710930>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Malignant rhabdoid tumor. A study with two established cell lines

Abstract: Background. Malignant rhabdoid tumor (MRT), originally described as a rare renal sarcoma in childhood, has been known to express phenotypic diversity. In this study, unique characteristics of the MRT cells were investigated by using established cell lines. Methods. Immunocytochemical, ultrastructural, cytogenetic, and molecular (by polymerase chain reaction, PCR) analyses were done for two MRT cell lines, one of renal and one of extrarenal origin, before and after differentiation‐induction with either 12‐O‐tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 34 publications
2
61
0
1
Order By: Relevance
“…Previous studies have shown that NSC acting as CSC is recognized in CNS (24)(25)(26)(27)(28)(29). In the present study, we examined the expression of NSC markers such as CD133, nestin and Msi-1 before and after 4-HPR induced differentiation in MRT cell lines to elucidate the cytological characteristics of MRT cells that are considered to derive from neuroectodermal origin (8,9,12).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies have shown that NSC acting as CSC is recognized in CNS (24)(25)(26)(27)(28)(29). In the present study, we examined the expression of NSC markers such as CD133, nestin and Msi-1 before and after 4-HPR induced differentiation in MRT cell lines to elucidate the cytological characteristics of MRT cells that are considered to derive from neuroectodermal origin (8,9,12).…”
Section: Introductionmentioning
confidence: 95%
“…Primary MRT also has been described in the central nervous system (CNS), paravertebral regions, pelvis, liver, orbit and ovary as well as the kidney (2)(3)(4)(5)(6)(7). A characteristic feature of MRT cells is the presence of large cytoplasmic eosinophilic inclusions (8,9). In the brain, the tumors may present as a mixture of rhabdoid, primitive neuroectodermal, mesenchymal and/or epithelial elements, an entity referred to as atypical teratoid/rhabdoid tumors (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumors are composed of large polygonal cells with eccentrically placed nuclei, and demonstrate an intracytoplasmic paranuclear eosinophilic condensation which compresses the nucleus [2]. Electron microscopy and immunohistochemical analysis has confirmed that these eosinophilic paranuclear condensations are composed of intermediate filaments [3]. Uncondensed chromatin and prominent nucleoli can often be found within the nuclei of the tumor cells [2,3].…”
Section: Introductionmentioning
confidence: 95%
“…The intracytoplasmic paranuclear condensations present in the rhabdoid cells are composed of intermediate filaments [3]. Most commonly, these are keratin filaments and can be highlighted by low and high molecular weight keratin immunohistochemical stains [24,25].…”
Section: Case Reportmentioning
confidence: 99%